2021
DOI: 10.3390/ijerph18179194
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Outbreak on Syncope Units Activities in Italy: A Report from the Italian Multidisciplinary Working Group on Syncope (GIMSI)

Abstract: The aim of our study was to evaluate the impact of the COVID-19 outbreak on Syncope Units (SUs) Activities in Italy. Methods: Data about types of SU activities and admissions were obtained from 10 SUs throughout Italy, certified by the Italian Multidisciplinary Working Group on Syncope (GIMSI), from 10 March 2020 to 31 December 2020 and compared with the same time frame in 2019. Results: A remarkable reduction in overall non-invasive diagnostic tests (−67%; p < 0.001) and cardiac invasive procedure. Electiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Moreover, the delay from STEMI diagnosis to primary PCI was 3 hours and 23 minutes showing the increased difficulty to correctly apply the protocols provided by the international guidelines for the management of cardiovascular diseases during the COVID-19 outbreak. 24 A position statement of the European Association of Percutaneous Cardiovascular Interventions (EAPCI) states the possibility of a delay in urgent revascularization procedures caused by prolonged time of arrival of the ambulance to the hospital, due to congestion and multiple calls because of the pandemic. In this scenario, PCI pathways in a COVID-19 patient with STEMI may be delayed up to 60 min beyond the 2-hour guidelines; 25 however, an immediate and complete revascularization to avoid staged procedures is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the delay from STEMI diagnosis to primary PCI was 3 hours and 23 minutes showing the increased difficulty to correctly apply the protocols provided by the international guidelines for the management of cardiovascular diseases during the COVID-19 outbreak. 24 A position statement of the European Association of Percutaneous Cardiovascular Interventions (EAPCI) states the possibility of a delay in urgent revascularization procedures caused by prolonged time of arrival of the ambulance to the hospital, due to congestion and multiple calls because of the pandemic. In this scenario, PCI pathways in a COVID-19 patient with STEMI may be delayed up to 60 min beyond the 2-hour guidelines; 25 however, an immediate and complete revascularization to avoid staged procedures is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Several observational studies described the impact of the COVID-19 outbreak on cardiac pacing and electrophysiology activities during the first lockdown in Italy (Figure 1). [4,5], Veneto region [6], AIAC survey [7] and a multicentre study from Italian Syncope Units [8]. Each cell shows the percentage reduction in hospitalizations for a specific procedure compared to the pre-pandemic period, followed respectively by the absolute number of procedures in the pre-COVID 19 A retrospective multicenter study [4], carried out in Campania region, the most-populous region of Southern Italy with about 5.8 million residents, showed a significant reduction in the rate of all cardiac implantable electronic devices (CIEDs) implantations and in cardiac resynchronization therapy (CRT) and device replacements (p-value < 0.05), more likely because of the reduction in planned hospitalizations following Italian government measures to contain SARS-CoV-2 in-hospital diffusion.…”
Section: Cardiac Pacing Proceduresmentioning
confidence: 99%
“…A retrospective multicenter observational study including 10 Italian Syncope Units (SUs), certified by the Italian Multidisciplinary Working Group on Syncope (GIMSI), suggested that COVID-19 lockdown was associated with a significant reduction rate in all the clinical activities related to the differential diagnosis of transient loss of consciousness (from 141 to 51 (−63%), p-value 0.001). The remarkable changes in the third-level SUs activities were more likely due to the reduction of patients referred from other hospital wards, which were converted into COVID-19 care centers [8].…”
Section: Syncope Unit Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempting to contain the virus spread, the Italian Government adopted strict rules, including the national lockdown from 9 March 2020 to 17 May 2020 [4]. During this period, non-urgent clinic visits or cardiac interventional procedures were postponed to a later date and changes in the patterns of hospital admissions in Italy were observed [5][6][7][8]. To date, no data have been provided on the adherence to cardiovascular (CV) pharmacotherapy during the COVID-19 outbreak.…”
Section: Introductionmentioning
confidence: 99%